Monetary policy responses to the recent crisis: Federal Reserve vs. European Central Bank - Ferreira, Leonor Mateus (2015)
In responding to the recent crisis, the American and European central banks implemented unlike approaches to monetary policy with different results. In order to understand their decisions and their actual outcomes, as well as prepare further situations like this one, it matters to analyze the monetary policy measures undertaken by both central banks and compare them. The present work particularly focus on unconventional monetary policy measures and examines credit easing implemented by the European Central Bank, in comparison to the Federal Reserve Bank’s quantitative easing. The results, emphasizing the decrease in bond yields due the increase in the banks’ balance sheets, the capacity to control inflation and unemployment and the ability to enhance production, reveal that the Fed was more effective and prompt in taking action against the crisis. In addition, the Fed was also more successful in its communications, with a better management of expectations, capacity to adapt to the markets’ response to quantitative easing and faster implementation of forward looking guidance, a feature determinant to the success of monetary policy. Moreover, the differences between the two banks that may limit the implementation of unconventional monetary policy measures and comprise additional challenges for the ECB are also discussed.